2019
DOI: 10.1111/1346-8138.15184
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells: The driver of psoriasis

Abstract: Psoriasis is a chronic skin inflammatory disorder, the immune mechanism of which has been profoundly elucidated in the past few years. The dominance of the interleukin (IL)-23/IL-17 axis is a significant breakthrough in the understanding of the pathogenesis of psoriasis, and treatment targeting IL-23 and IL-17 has successfully benefited patients with the disease. The skin contains a complex network of dendritic cells (DC) mainly composed of epidermal Langerhans cells, bone marrow-derived dermal conventional DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 149 publications
(218 reference statements)
0
96
0
2
Order By: Relevance
“…Activated DCs played a pivotal role in psoriasis pathogenesis. They not only initiated the in ammation, but also sustained it [15] . Activated mast cells were elevated in psoriatic plaque and produced IL-17, IL-22 [16] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Activated DCs played a pivotal role in psoriasis pathogenesis. They not only initiated the in ammation, but also sustained it [15] . Activated mast cells were elevated in psoriatic plaque and produced IL-17, IL-22 [16] .…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the severity of psoriasis was indicated by Psoriasis Area and Severity Index (PASI). Based on PASI, the severity was classi ed into three levels: mild (0-12), moderate (12)(13)(14)(15)(16)(17)(18) and severe (> 18) ( Table. 1). Among these innate immune cells, proportion of M0 macrophages and resting mast cells showed correlation with disease severity (Figure. 2).…”
Section: Association Between Innate Immune Cells and Clinical Manifesmentioning
confidence: 99%
“…The skin contains a complex network of DCs mainly composed of epidermal Langerhans cells (LCs), bone-marrow-derived dermal conventional DCs (cDCs), pDCs, and inflammatory DCs (iDCs) [ 25 ]. As the prominent cellular source of IFNα, TNFα, IL12, and IL23, DCs play an important role in psoriasis [ 25 ].…”
Section: Pathogenesis Of Psoriasismentioning
confidence: 99%
“…pDCs originate in the bone marrow and migrate to the skin under pathologic conditions [ 25 ]. pDCs recognize viral nucleic acids and produce large amounts of type I IFNs in response to endosomal Toll-like receptors (TLRs), such as TLR7 and 9 [ 26 , 27 , 28 , 29 ].…”
Section: Pathogenesis Of Psoriasismentioning
confidence: 99%
“…The current model of psoriasis pathogenesis considers that it is the crosstalk between the complex network of skin DCs, T cells (mainly Th17 [87]) and resident KCs that generate inflammatory and immune routes which are responsible for the initiation, progression and persistence of the disease [73,85,88]. Thus, psoriasis seems to arise in genetically predisposed individuals with an abnormal innate and adaptive immune response to environmental factors that results in a hyperproliferation of KCs, but the exact mechanisms behind these are not completely understood [89,90].…”
Section: The Pathogenesis Of Psoriasismentioning
confidence: 99%